Pengaruh Akuntabilitas dan Kualitas Laporan Keuangan terhadap Kinerja Pemerintah Daerah - Azima Hanisa; Dian Fitria Handayani (Universitas Negeri Padang, 2023)
The purpose of this research is to examine the effect of accountability and the quality of financial reports on the performance of local government in Sijunjung District. The population of this research is 35 OPD in Sijunjung Regency. The respondents were the head of OPD, the treasurer, and the finance department. This research used a questionnaire distributed to 140 respondents. The results of this research indicate that 1) accountability has a positive effect on the performance of local government in Sijunjung Regency 2) the quality of financial reports has a positive effect on the performance of local government in Sijunjung Regency. The contribution of the independent variables in explaining the dependent variable is 38.4% while the remaining 61.1% is explained by other variables not examined in this research. Suggestions for further research are suggested to add other variables such as organizational culture.